The Contribution of Teaching Practice to Preservice Teachers’ Training – Empirical Research of the Department of Primary Education of Western Macedonia University Students’ Evaluation - Pavlos Stavridis, Vasiliki Papadopoulou (Educational Process: International Journal)
Background/purpose – Teaching practice is an essential and integral part of preservice teacher training. In this study, we investigated its role in guiding and supporting student work, and whether or not it contributed to their successful completion of a teacher education program.